Articular and subcutaneous adipose tissues of rheumatoid arthritis patients represent equal sources of immunoregulatory mesenchymal stem cells. (17th November 2017) - Skalska, Urszula; Kuca-Warnawin, Ewa; Kornatka, Anna; Janicka, Iwona; Musiałowicz, Urszula; Burakowski, Tomasz; Kontny, Ewa
Abstract: Adipose-derived mesenchymal stem cells (ASCs) have immunoregulatory properties, but their activity is dependent on signals provided by the local microenvironment. It is likely that highly inflammatory milieu of rheumatoid joint affects ASCs activity. To test this hypothesis, the function of rheumatoid ASCs derived from articular adipose tissue (AT-ASCs) and ASCs derived from subcutaneous adipose tissue (Sc-ASCs) has been analysed. Articular adipose tissue (infrapatellar fat pad) and subcutaneous adipose tissue (from the site of skin closure with sutures) were obtained from rheumatoid arthritis (RA) patients undergoing total knee joint replacement surgery. ASCs were isolated accordingly to the routinely applied procedure, expanded and treated or not with IFNγ and TNF (10 ng/ml). To evaluate immunomodulatory properties of AT- and Sc-ASCs, co-cultures with peripheral blood mononuclear cells (PBMCs) from healthy donors have been set. Proliferation of activated PBMCs ( 3 H-thymidine incorporation method), secretion of IL-10 and IL-17A in co-culture supernatants (specific ELISA tests) and T regulatory FoxP3 + cells (Tregs) percentage have been evaluated (flow cytometry). Performed experiments demonstrated that ASCs from both sources have comparable properties. They suppress proliferation of activated PBMCs to the similar extent, induce IL-10 secretion by resting PBMCs and moderately induce generation of FoxP3 + Treg cells. Interestingly, both AT-ASCs and Sc-ASCs cause increase of IL-17A secretion by activated PBMCs as well as induce up-regulation of IL-6 concentration in co-culture supernatants. We demonstrated that AT-ASCs and Sc-ASCs obtained from RA patients possess similar immunomodulatory properties despite different localization and distinct cytokine milieu of tissue of origin. Our results indicate that ASCs derived from rheumatoid adipose tissues are not strongly immunosuppressive in vitro and that they may contribute to the pathogenesis of RA due to IL-17A secretion enhancement.